Socioeconomic inequalities in the use of skilled birth delivery during childbirth in Ghana: a decomposition model - Kpodotsi, Aseye (Department of Public Health and Family Medicine, 2019)
Equitable access to, and use of skilled birth attendance during delivery is vital for the achievement of the Sustainable Development Goals (SDGs) in reducing global maternal deaths to 70 deaths per 100, 000. Although several initiatives have been implemented to reduce maternal mortality in Ghana, inequities in the use of skilled birth attendance during delivery still exist among women of different socioeconomic groups. This study assessed the socioeconomic inequalities and the underlying factors related to the inequalities in the use of skilled birth attendants during delivery in Ghana. This study analysed data from the 2014 Ghana Demographic and Health Survey (GDHS) using a decomposable health concentration index. Concentration index (CI) and concentration curves were employed to measure the magnitude of socioeconomic inequality in the use of skilled birth attendants during child delivery. The concentration index was decomposed to identify the underlying factors causing the inequalities. Out of a total of the 1,305 women who gave birth in the year prior to the interview, 28% of the deliveries had no skilled birth attendants of which 60% lives in rural compared to 40% in urban. A concentration index of 0.147 showed a pro-rich utilization of skilled birth attendance during delivery. The decomposition analysis revealed that, wealth, education and location of residence were the major contributors to socioeconomic inequalities in the use of skilled birth attendants during child delivery among Ghanaian women. This study suggests that factors such as wealth, area of residence and education are worthy of increased attention in programmatic efforts, and policy interventions, because they are amenable to the reduction of observed inequality.